Energy‐resolved technique for discovery and identification of malonyl‐triterpene saponins in Caulophyllum robustum by UHPLC‐electrospray Fourier transform mass spectrometry. (6th September 2016) - Xia, Yong‐Gang; Liang, Jun; Li, Guo‐Yu; Yang, Bing‐You; Kuang, Hai‐Xue
Abstract : Malonyl‐triterpene saponins (MTSs) attract scientific attentions because of their structural diversities and valuable bioactivities. However, its thermal instability brings a huge amount of challenges for isolation and purification of this class of compounds. To our best knowledge, there has been no report on isolation and analysis of MTSs from genus Caulophyllum . In this study, a strategy combining data acquisition using an energy‐resolved technique and the narrow widow extracted ion chromatograms as data mining method was developed for discovery and identification of MTSs in Caulophyllum robustum hair roots by ultra high liquid chromatography coupled to electrospray ionization Fourier transform mass spectrometry. The method was performed at an independent MS full scan using our bottom‐up energies by in‐source collision induced dissociations with 0, 25, 50 and 100 eV in both positive and negative modes. Precursor ion as well as fragment ion information was simultaneously collected from four energy‐resolved MS spectra in a single run of 18 min. The fragmentation pathways of intact deprotonated, protonated and sodium ions of MTSs were proposed for the structural elucidation of Caulophyllum MTSs. A flowchart involving a stepwise procedure based on key fragments from ESI − /ESI + ‐FT‐MS (1, 1) to MS (1, 4) spectra was constructed for the identification of structural elements in the MTSs. As a result, a total of 23 MTSs were discovered and tentatively identified, which had not been reported from Caulophyllum species before. All of these were potentially new compounds. This study provides an excellent example for discovery and identification of MTSs in herb medicines. Copyright © 2016 John Wiley & Sons, Ltd.